Tissue Engineering of Large Full-Size Meniscus Defects by a Polyurethane Scaffold: Accelerated Regeneration by Mesenchymal Stromal Cells - Matthias Koch; Felix P. Achatz; Siegmund Lang; Christian G. Pfeifer; Girish Pattappa; Richard Kujat; Michael Nerlich; Peter Angele; Johannes Zellner (Stem Cells International)
The endogenous healing potential of avascular meniscal lesions is poor. Up to now, partial meniscectomy is still the treatment of choice for meniscal lesions within the avascular area. However, the large loss of meniscus substance predisposes the knee for osteoarthritic changes. Tissue engineering techniques for the replacement of such lesions could be a promising alternative treatment option. Thus, a polyurethane scaffold, which is already in clinical use, loaded with mesenchymal stromal cells, was analyzed for the repair of critical meniscus defects in the avascular zone. Large, approximately 7 mm broad meniscus lesions affecting both the avascular and vascular area of the lateral rabbit meniscus were treated with polyurethane scaffolds either loaded or unloaded with mesenchymal stromal cells. Menisci were harvested at 6 and 12 weeks after initial surgery. Both cell-free and cell-loaded approaches led to well-integrated and stable meniscus-like repair tissue. However, an accelerated healing was achieved by the application of mesenchymal stromal cells. Dense vascularization was detected throughout the repair tissue of both treatment groups. Overall, the polyurethane scaffold seems to promote the vessel ingrowth. The application of mesenchymal stromal cells has the potential to speed up the healing process.